CITY WEDDINGS IN DAGHESTAN: A NEW VERSION OF OLD TRADITION, OR ADAPTATION TO GLOBAL TRENDS OF URBANIZATION? - Мусаева, Майсарат Камиловна; Гарунова, Саида Магомедхановна; Ченсинер, Роберт (History, Archeology and Ethnography of the Caucasus, 2018)
Daghestan’s urban culture, in its Russian–European variety, is a relatively new phenomenon. Until the 1970’s, weddings in cities have been celebrated only by hereditary citizens, i.e. Russians, Armenians, Jews, Azerbaijanis, Kumyks, occasionally, while the rest of the city residents preferred to go to their home villages and play weddings there, after which the bride and groom would return if they were going to live in the city. Since the 1990’s, with the growth of the urban population due to the influx of the rural population, this tradition has disappeared in Daghestan, as rural residents often have to come to the city to celebrate the wedding.This article is based on ethnographic materials identified through field observation included. The authors focus on the presentation of the preserved traditional elements of urban wedding rituals and the new ritual and other components that have appeared in recent decades. The analysis of the modern family and public holiday, which the wedding has always been for the peoples of Daghestan, demonstrates the close connection between local traditions and Russian-European innovations, under the influence of various factors. Modern city weddings in Daghestan find in different cities a different ratio between the secular and Islamic components in wedding ceremonies. The authors consider the modern wedding in the cities of Daghestan as a multicomponent ceremony, consisting traditionally of preliminary preparations, the wedding itself and the ceremonies after the wedding.The innovations used in urban wedding rituals are an expression of value orientations, ethnic, ethical, aesthetic, and ethnocultural preferences of modern Daghestan citizens.Under the conditions of ethnocultural dynamics influenced by the intensive migration of the population from the mountains to the plain, where all the modern Daghestan cities are located, the “urban culture” radically transforms not only the marriage traditions, but also the very perception of these traditions. A look at the ratio of the traditional and the modern in the urban wedding rituals is now in each generation its own. And perhaps it is partly subjective and needs to be discussed.
Keywords: Daghestan; Daghestanis; urbanization; urban ethnography; city weddings; marriage customs; marriage attitudes.